Perspective of medical graduates from Patan Academy of Health Sciences on the management of COVID-19, during the initial phase of pandemic in Nepal - Shrestha, Shrijana; Shrestha, Ashis; Acharya, Balakrishnan M (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Nepal, with a poor health infrastructure and resources, when hit by the COVID-19 pandemic in 2020, the health system and the health workers were not well prepared to handle the crisis. Method: A survey was conducted during the initial phase of the pandemic (July-October, 2020) to understand the perspective of PAHS medical graduates on the management of COVID-19. A survey questionnaire was prepared in Google Form and circulated through official group emails. Result: A total of 80 graduates participated in the survey .Of the participants, 35(66%) reported that their health facility was only partially prepared and 8 (15.1%) reported that their site was not at all prepared to take care of COVID-19 patients. The local government and the community of their workplace were reported as supportive of the efforts of the pandemic management by 30(37.7%) and 33(41.5%) respondents respectively. The graduates working during the pandemic were involved in activities like swab collection (8), screening (30), critical care (37), patient education/counseling (41), managing non-COVID-19 patients (47), and administrative work (17). Inadequate planning of service delivery was identified as major lacking nationally while the human resources, logistics, PPE and lack of motivation were reported as the major lacking locally by the participating graduates. Conclusion: The fresh PAHS graduates were found to be contributing at their respective workplaces fitting into both the clinical and non-clinical roles during the initial phase of the pandemic in Nepal. They reported that one or more of the components of PAHS training helped in the readiness to work in this pandemic.